Expanding Boundaries : the Impact of the Special Education in Scotland Program. - Johnson, Laura E. (My University, 2009)
Special Education (SPED) in Scotland is a six-week study abroad program where pre-service special eduation teachers lived with host families and observed in Scottish schools in the area of special education. This study sought to determine the impact of SPED in Scotland on students' intercultural awareness, self-efficacy in educational practices, and awareness of global interconnectedness.
Color poster with text and images describing research conducted by Laura E. Johnson, advised by Rosemary L. Battalio.
Keywords: Special education--Scotland; Special education--Cross-cultural studies; Special education teachers--Training of; Foreign study--Scotland; Posters